Can democratic values bring the parties to the table in a protracted, Middle Eastern conflict? The attitudes of youth in the context of the Arab- Israeli conflict. Issue 4 (19th May 2022) - Khatib, Ibrahim
ABSTRACT: How do democratic values affect the willingness of parties to reconcile in the context of protracted conflict? Based on a survey of 2171 students conducted in Israel, Palestine, Egypt, Jordan, and Tunisia between 15 November 2015 and 10 March 2016, the results indicate that democratic values and the willingness to reconcile are not necessarily positively correlated; in fact, in some cases, the correlation is negative. The main argument of this article is that neither democratic values nor democratic regimes can guarantee reconciliation or peace, but liberal democratic values and democratic regimes working together can decrease or even help reject the unwillingness to reconcile. The value of justice, just solution, protected values, threat perception, interests, nature and reality of the regime for example, can also explain peaceful attitudes. Finally, this article theorizes that individual and state level actors working together can contribute to understanding democratic peace processes and reconciliation between countries.